Autoimmune Diseases and Psychotic Disorders - Jeppesen, Rose; Benros, Michael Eriksen (Frontiers in Psychiatry, 2019)
The notion of immunological pathways playing a role in the etiology of a subset of psychotic disorders has received increased interest in the last decades. One of the findings that has spiked interest herein, is an apparent link between autoimmune diseases and psychotic disorders. This is supported by genetic findings associating immune-related genetic markers with schizophrenia and clinical studies finding increased levels of inflammation markers in patients with psychosis. Several large-scale epidemiologic studies have found positive associations between autoimmune diseases and psychosis. Particularly autoimmune diseases as multiple sclerosis and lupus are known to have higher frequencies of neuropsychiatric symptoms, including psychosis, compared to healthy controls. Cross sectional studies have found higher prevalence of psychiatric diagnoses among those with autoimmune diseases, and longitudinal studies have shown bidirectional associations between several autoimmune diseases and increased risks associated with schizophrenia. Moreover, a family history of autoimmune diseases has been shown to be associated with an increased risk of psychotic disorders and vice versa. In this review we will summarize the epidemiologic evidence on associations between autoimmune diseases and psychosis. Possible mechanisms accountable for the association will be discussed, amongst others the probable role of shared genetic risk factors, the impact of infections of both autoimmunity and the development of psychotic disorders, and the potential role of the microbiome. We discuss the findings on and influence of autoantibodies and dysregulation of T- and B-cells in both disease categories, and why further research hereon is needed. In addition to the potential importance of autoimmunity as etiological mechanisms of psychotic disorders, the association also brings important attention to somatic comorbidity in patients with psychotic disorders.